Association of shorter telomeres with coronary artery disease in Indian subjects. Issue 8 (21st November 2008) - Mukherjee, M; Brouilette, S; Stevens, S; Shetty, K R; Samani, N J
Abstract : Objective: Studies in white people have shown that telomere length, a marker of biological ageing, is shorter in individuals with coronary artery disease (CAD). South Asian Indians have a high prevalence of CAD, especially premature CAD. We examined the association of telomere length with CAD in Indian subjects. Design: Case-control study. Setting: Mumbai, India. Subjects: 238 consecutive patients (aged 29–82 years), admitted to Cumballa Hill Hospital for coronary investigations or treatment and 238 control subjects (aged 30–87 years) from the same area without any clinical evidence of CAD. Methods: Mean leucocyte telomere length was measured using a polymerase chain reaction (PCR)-based assay and expressed as a ratio (T/S ratio) of the telomere signal to that of a control single copy gene. Results: T/S ratio was significantly lower in CAD cases compared with controls (cases 1.21 (95% CI 1.16 to 1.26); controls 1.33 (1.28 to 1.38); p = 0.0003), equivalent to approximately 166 base pairs. The difference remained significant after adjustment for other clinical characteristics (p = 0.002). There were trends towards longer telomeres in vegetarian subjects compared with subjects on a mixed diet (vegetarians 1.31 (1.25 to 1.38); mixed 1.25 (1.18 to 1.33); p = 0.088) and shorter telomeres in subjects with a positive family history (FH) for CAD (+ve FH 1.25 (1.18 to 1.32); -ve FH 1.31 (1.24 to 1.38); p = 0.094). Conclusion: Subjects of Indian ethnicity with CAD have shorter telomeres than subjects without such a history. The finding provides further evidence that telomere biology is altered in subjects with CAD.